A comparison investigation of the contact models for contact and vibration features of cylindrical roller bearings. Issue 5 (18th June 2019) - Liu, Jing; Wang, Linfeng; Shi, Zhifeng; Yu, Wennian; Xiao, Huifang
Abstract : Purpose: The purpose of this study is to investigate the contact models for contact and vibration features of cylindrical roller bearings (CRBs). CRBs are important parts of rotating machinery. The contact deformation between the roller and the raceway is an essential research topic for the CRBs. The contact deformation between the roller and the raceway can greatly affect vibration characteristics and fatigue life of the CRBs. In this investigation, six different methods are adopted to calculate the contact deformation, contact area width and contact stress between the roller and raceways of a CRB. Design/methodology/approach: In this paper, the contact deformations and the contact stiffnesses between the roller and the raceway of a CRB obtained by various well-known empirical methods (Lundberg's, Palmgren's, Houpert's, Cheng's and Hertzian methods) are directly compared with those by the finite element (FE) method. A two degree-of-freedom (2 DOF) dynamic model of the CRB is applied to investigate the effects of the contact stiffness obtained by different line contact deformation calculation methods on the vibration characteristics, such as the root mean square (RMS), the peak to peak (PTP), the crest factor and the kurtosis of the displacement, velocity and acceleration of the inner raceway. Findings: The computational results show that different calculation methods for the contact deformations between rollers and raceways have significant effects on the vibrations of the CRB. It is found that that the differences of computational results obtained by Palmgren's and Lundberg's models with respect to the FE method are smaller than those by the other three methods, i.e. Houpert's, Cheng's and Hertzain models. The amplitude and peak frequency of the frequency response functions from Palmgren's method are much more similar to those from the finite element method. The above results indicate that Palmgren's method is a better calculation method for predicting the contact deformations and dynamics of the CRBs. Originality/value: This work adopts six different methods to calculate the contact deformation, contact area width and contact stress between the roller and raceways of a CRB. Moreover, a vibration model of a CRB is used to investigate the effect of contact stiffness obtained by the above methods on the vibrations of the CRB. The works can give some guidance for the accurate analytical method for calculating the contact deformations between rollers and raceways and the vibrations of the CRB.